Fatores associados à dor dentaria em adolescentes de 12 anos no estado de Minas Gerais e educação em saúde como ferramenta de enfrentamento aos problemas de saúde bucal - Nildelaine Cristina Costa (2021)
Toothache is often described as the most frequent type of orofacial pain. It has a significant impact on people's lives and society. This can be avoided through effective strategies, including prevention and intervention. The main causes of toothache are caries, periodontal diseases and dental trauma. Adolescence is a transitional phase characterized by intense physical and psychological changes, in which individuals can engage in behaviors that can compromise their health. Adolescents are, therefore, a vulnerable population group that requires adequate care according to their individual, family and social context, which can influence their general and oral health. Literature has shown that toothache is associated with socioeconomic, family, cultural, behavioral and psychosocial factors. There are studies on the prevalence of toothache in adolescents, however, for Minas Gerais, Brazil, there is no study with a multilevel approach. The main objective of this cross-sectional study was to assess which contextual and individual factors are associated with toothache in adolescents (12 years old) from the state of Minas Gerais, located in the southeast region of Brazil, in addition to developing a technical product aimed at preventing toothache. This study used secondary data from the epidemiological database of SB Minas 2012. Dependent variable was toothache reported in the last six months. The covariates were grouped in two levels, individual (sex, self-reported ethnic group, family income (values in reais), periodontal condition, dental caries, need for dental treatment, type of service used). The contextual variables were Allocation factor (interior I, interior II, capital), HDI, Gini Coefficient, Gross Domestic Product, Unemployment, Illiteracy, Family income per person, Half the minimum wage, One quarter of the minimum wage, Sanitary Sewage, Garbage Collection, Primary Health Care Coverage (APS), Coverage of Oral Health Teams in APS, Presence of Oral Health Technician, Coverage of 1st appointment, Supervised brushing. These covariates were analyzed at the regional level of the state. Data were analyzed in the IBM SPSS Software version 22.0 program. A multilevel logistic regression statistical model (OR – 95%CI) was carried out to assess the association between the different levels, considering 5% significance. The prevalence of dental pain was 19.1% and was associated with family income (p <0.001), dental caries (p <0.001), coverage of the Oral Health Team in PHC (p = 0.015) and presence of a Health Technician Oral in ESB (p = 0.008). Socioeconomic conditions and the use of dental services were associated with toothache. The results of this study reinforce the need to formulate more effective public strategies. Regarding the technical product, the idea was to prepare educational material to be published in media with a large circulation of people. The main themes were oral health care and how to prevent oral problems such as caries, periodontal diseases, oral cancer, dental trauma and edentulism. The illustrations were done in Canva's design and template program. It is an educational product, easy to replicate, low cost, with great social reach and with the potential to promote positive changes in individual and collective behavior in dealing with oral problems.